Plant Reintroduction in a Changing Climate Promises and Perils - Maschinski, Joyce; Haskins, Kristin E.; Raven, Peter H.; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2012)
Considered an essential conservation tool, plant reintroductions have been conducted for many of the world's rarest plant species. The expertise and knowledge gained through these efforts constitute an essential storehouse of information for conservationists faced with a rapidly changing global climate. This volume presents a comprehensive review of reintroduction projects and practices, the circumstances of their successes or failures, lessons learned, and the potential role for reintroductions in preserving species threatened by climate change. Contributors examine current plant reintroduction practices, from selecting appropriate source material and recipient sites to assessing population demography. The findings culminate in a set of Best Reintroduction Practice Guidelines, included in an appendix. These guidelines cover stages from planning and implementation to long-term monitoring, and offer not only recommended actions but also checklists of questions to consider that are applicable to projects around the world. Traditional reintroduction practice can inform managed relocation-the deliberate movement of species outside their native range-which may be the only hope for some species to persist in a natural environment. Included in the book are discussions of the history, fears, and controversy regarding managed relocation, along with protocols for evaluating invasive risk and proposals for conducting managed relocation of rare plants. Plant Reintroduction in a Changing Climate is a comprehensive and accessible reference for practitioners to use in planning and executing rare plant reintroductions.
1. Introduction -- 2. Characterizing Two Decades of Rare Plant Reintroductions -- 3. A Meta-Analysis of Threatened Plant Reintroductions from across the Globe -- 4. The Critical Role of the Public: Plant Conservation through Volunteer and Community Outreach Projects -- 5. Genetic Considerations in Rare Plant Reintroduction: Practical Applications (or How Are We Doing?) -- 6. Transitioning Plants to New Environments: Beneficial Applications of Soil Microbes -- 7. Optimal Locations for Plant Reintroductions in a Changing World -- 8. Strategic Decisions in Conservation: Using Species Distribution Modeling to Match Ecological Requirements to Available Habitat -- 9. Using Population Viability Analysis to Plan Reintroductions -- 10. Influence of Founder Population Size, Propagule Stages, and Life History on the Survival of Reintroduced Plant Populations -- 11. Determining Success Criteria for Reintroductions of Threatened Long-Lived Plants -- 12. Unique Reintroduction Considerations in Hawaii: Case Studies from a Decade of Rare Plant Restoration at the Oahu Army Natural Resource Rare Plant Program -- 13. Managed Relocation: Panacea or Pandemonium? -- 14. Is Managed Relocation of Rare Plants Another Pathway for Biological Invasions? -- 15. Synthesis and Future Directions -- Appendix 1: Center for Plant Conservation Best Reintroduction Practice Guidelines -- Appendix 2: Studies Used for Meta-Analyses -- Glossary -- Literature cited -- Contributors -- Index.
Keywords: Environmental sciences; Biodiversity; Plant Ecology; Conservation biology; Climatic changes; Nature Conservation; Environment; Climate Change; Nature Conservation; Plant Ecology; Biodiversity; Conservation Biology/Ecology.